Identification of potential areas for upwelling based on characteristics of eddies event in the Bone gulf. Issue 1 (1st December 2022) - Hidayat, R; Zainuddin, M; Safruddin,; Wiyono, E S
Abstract: The Bone Gulf is one of the waters with massive potential for catching pelagic fish. The potential for catching fish is associated with oceanographic events in the waters. This study aims to see the potential for upwelling in the eddy occurrence areas. The spatial analysis method will be used to see the potential for upwelling in the area of the eddy occurrence and will be associated with sea surface temperature parameters and chlorophyll-a as a fertility variable. The results of this study indicate that eddy events occur every month in the Bone Gulf waters. In addition, it can be proven that every eddy occurrence is not a guarantee for the emergence of upwelling areas simultaneously. However, several eddy events with high current velocities were seen to cause a decrease in temperature in the middle of the eddy and increase the chlorophyll-a concentration in that area. In addition, the suitability of this event is also shown from the time of upwelling, which occurs several months before the peak month of fishing in the Bone Gulf. This research is expected to be the basis for the sustainable development of fisheries.